Helminth therapies: translating the unknown unknowns to known knowns. - FALLON, PADRAIC (My University, 2013)
The use of live helminth infections is currently in clinical trials as a novel approach for the treatment of a range of allergic and autoimmune diseases. This rapid progression from observational studies some 20 years ago to helminth clinical trials can be attributed to huge advances in not just pre-clinical and clinical evidence, pertaining to the efficacy of these parasites in unrelated diseases, but also a greater understanding of the complex immunological mechanisms that underpin these effects. Helminths have exerted significant evolutionary selective pressures on the host immune genome or “immunome”. Studies on helminths were pivotal in a paradigm shift in immunology with recent discoveries of a number of novel immune cell populations. Critically, these new discoveries highlight the need to further understand the underlying mechanism behind the desirable therapeutic effects that helminths offer. With these unknown unknowns there is the distinct possibility that a true, fundamental modus operandi for helminth therapy will arrive long after it has been established in the clinic.
PUBLISHED
Keywords: Helminth infections; Immunology, Inflammation & Infection; Biomedical sciences